(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2026)
In addition to the high sugar and high fat, processed food containing high salt is considered detrimental to the worldwide obesity epidemic. The present study aimed to investigate the effect of a modified diet with high-salt (4% NaCl) on fat deposition in high-fat diet-induced obese mice. Forty healthy Swiss Albino mice (Sex: Female) were taken and divided equally into two groups named the non-obese group and the obese group. To induce obesity, mice were fed a high-fat diet. The non-obese and obese mice were further subdivided into four groups depending on their feed, i.e., normal diet, a normal diet with high salts, a high-fat diet, and a high-fat diet with high salts. Central obesity was determined by monitoring body weight and Lee index. Furthermore, different organ weights, serum triglycerides, total cholesterol, high-density lipoprotein, and low-density lipoprotein levels were assessed. Liver function was monitored by analyzing SGOT and SGPT. The high-fat diet was able to induce adiposity and increase the obesity-related parameters significantly. Treatment with high salts along with high fat showed a significant (p < 0.05) reduction in obesity and in the parameters tested, except for the significant (p < 0.05) elevation of high-density lipoprotein compared with their controls. The results of this study predicted that a high salt (4% NaCl) diet has an inhibitory action on fat absorption, which might be effective to attenuate the central obesity and obesity-related parameters. Dhaka Univ. J. Pharm. Sci. 25(1): 1-10, 2026 (June)